Biomechanical analysis of the pole vault - Schade, F.; Arampatzis, A.; Brüggemann, G. P. (1998)
INTRODUCTION: The main purposes of this study were to (a) examine the behavior and practical application of 3 criteria in world class pole vaulters and (b) to determine the influence of the starting conditions and athlete's behavior during the pole phase, on performance. Note that the three criteria label the starting conditions of the pole vault and the behavior of athletes during the pole phase. METHODS: Data for this study were gathered at the 1997 Track and Field World Championships in Athens, Greece. Twenty-five successful jumps by 11 participants in the final competition were analyzed. The data for the two-dimensional analysis were recorded using two synchronized stationary video cameras operating at 50 Hz. For the analysis of the data, the pole vault was divided into (a) energy production phase (This phase begins with the approach and ends with the contact of the jump foot and the ground at take-off.) and (b) energy exchange phase (This phase begins with contact of the jump foot and the ground at take-off and ends when the athlete releases the pole at the end of the jump.). RESULTS AND CONCLUSIONS: During the first part of the energy exchange phase, energy is transferred into the pole, reducing the athlete's total energy. The difference between the decrease of the athlete's total energy and the maximum pole energy indicates whether pole elasticity was effectively used (Criterion 1) (see Figure 1). During the second part of the energy exchange phase, the energy is transferred back from the pole to the athlete, increasing the athlete's total energy. The difference between the returned energy and the energy gain of the athlete indicates to what extent the athlete used muscular work to create additional energy (Criterion 2). The approach energy (start energy) represents the starting conditions of the pole vaulter (Criterion 3). From the analyzed jumps, it was possible to create 3 groups which demonstrated similar values for start energy, Criterion 1 and Criterion 2. The results indicate that both individual and group-specific technique deficits of athletes can vary and still produce the same performance. At the elite level, the start energy determines the beginning conditions for good or poor jump performance. The actual jump heights achieved are dependent on the behavior of the vaulter during the energy exchange phase. From the examination of the start energy, Criterion 1 and Criterion 2, it was possible to diagnose the individual technical deficits of the athletes.